2018
DOI: 10.1002/anie.201712520
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific ortho‐C−H Allylation of Benzoic Acids

Abstract: A carboxylate-directed ortho-C-H functionalization has been developed and it allows the regiospecific introduction of allyl residues to benzoic acids. In the presence of a [Ru(p-cymene)Cl ] and K PO , benzoic acids react with allyl acetates at only 50 °C to give the corresponding ortho-allylbenzoic acids. The protocol is generally applicable to both electron-rich and electron-poor benzoic acids in combination with linear and branched allyl acetates. The products can be further functionalized in situ, for examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 100 publications
1
28
0
5
Order By: Relevance
“…[95] As an alternative to allylic halides,t he Gooßen group showed that allylic acetates could be used for ac arboxylatedirected ortho-allylation of benzoic acids under ruthenium catalysis,w ith this procedure being compatible with both electron-rich and electron-poor substrates as well as linear and branched allyl acetates. [96] Mono-and bidentate amides actually represent the main directing groups utilized in such reactions:anoverview of the most efficient processes developed to date for the directed alkylation of aromatic amides with alkyl halides will be presented in the following section.…”
Section: Alkylation Of Benzoic Acids With Alkyl Halidesmentioning
confidence: 99%
“…[95] As an alternative to allylic halides,t he Gooßen group showed that allylic acetates could be used for ac arboxylatedirected ortho-allylation of benzoic acids under ruthenium catalysis,w ith this procedure being compatible with both electron-rich and electron-poor substrates as well as linear and branched allyl acetates. [96] Mono-and bidentate amides actually represent the main directing groups utilized in such reactions:anoverview of the most efficient processes developed to date for the directed alkylation of aromatic amides with alkyl halides will be presented in the following section.…”
Section: Alkylation Of Benzoic Acids With Alkyl Halidesmentioning
confidence: 99%
“…[95] Als Alternative zu Allylhalogeniden zeigte die Gruppe von Gooßen, dass Allylacetate füre ine carboxylatdirigierte ortho-Allylierung von Benzoesäuren unter Rutheniumkatalyse verwendet werden kçnnen, und zwar nach einer Vorschrift, die mit sowohl elektronenreichen als auch elektronenarmen Substraten ebenso wie linearen als auch verzweigten Allylacetaten kompatibel war. [96] Ein-und zweizähnige Amide repräsentieren die wichtigsten dirigierenden Gruppen, die in solchen Reaktionen eingesetzt wurden. Eine Übersicht über die effizientesten Verfahren, die bisher fürd ie dirigierte Alkylierung aromatischer Amide mit Alkylhalogeniden entwickelt worden sind, wird nachfolgend vorgestellt.…”
Section: Angewandte Chemieunclassified
“…[4] Despite indisputable advances by the groups of Mei, Sanford, and Ackermann, [5] electrochemical CÀHo xygenations [6] of challenging arenes by weak coordination [7] have thus far proven elusive.T he reported metalcatalyzed C À Ho xygenations largely require cost-intensive palladium complexes and were inherently limited to strongly coordinating N-directing groups,s uch as oximes and pyr-idines. [5] In sharp contrast, CÀHoxygenations by synthetically useful weak O-coordination have not been realized in terms of sustainable electrocatalysis.Instead, highly reactive hypervalent iodine(III) reagents, [8,9] such as (diacetoxyiodo)benzene and [bis(trifluoroacetoxy)iodo]benzene,a re required in overstoichiometric quantities,which calls for strong chemical oxidants for their synthesis and leads to equimolar amounts of undesired halogenated waste products during the CÀH functionalization process.C ontrarily,w eh erein present am echanistically distinct strategy to address this molecular challenge,w hich orchestrates the catalytic electro-regeneration [10] of hypervalent iodine(III) reagents with ruthenium-(II)-catalyzed [11,12] CÀHf unctionalizations ( Figure 1). Salient features of our findings include a) the first electrocatalyzed CÀHoxygenations by weak coordination, b) the user-friendly electrochemical generation of hypervalent iodine reagents, c) ioda/ruthena-electrocatalyzedC À Hfunctionalizations that combine the advantages of ruthenium-catalyzed C À Hactivation with electrocatalytic hypervalent iodine chemistry,a nd d) mechanistic studies by experiment, computation, cyclic voltammetry,a nd in operando NMR spectroscopy.…”
mentioning
confidence: 99%